GREEN HUMAN RESOURCE MANAGEMENT, EMPLOYEE BEHAVIOR, AND ORGANIZATIONAL INNOVATION: A MULTI-THEORETIC PATHWAY TO SUSTAINABLE COMPETITIVENESS - Perwira, Iwan; Hernita, Hernita; Suardi, Suardi; Sose, Andi Tenry; Azizurrohman, Muhammad (Journal of Environmental Science and Sustainable Development, 2025)
As sustainability imperatives reshape global tourism, this study investigates how Green Human Resource Management (GHRM) practices can serve as strategic levers for driving sustainability performance and competitive advantage within Indonesia’s tourism sector. Amid rising environmental expectations and regulatory mandates, the research integrates Social Learning Theory, the Resource-Based View, and Institutional Theory to construct and test a model that links top management support, green organizational culture, and regulatory pressure to GHRM adoption. Using a cross-sectional survey of 510 employees and managers across eco-certified tourism firms in five Indonesian destinations, the study employed Partial Least Squares Structural Equation Modeling (PLS-SEM) to analyze relationships among constructs. Findings revealed that GHRM practices foster both employee green behavior and organizational green innovation, two distinct internal mechanisms that jointly mediate the impact of HR systems on sustainability outcomes. These dual mediation pathways clarify how people-centered strategies transform environmental values into operational performance and market competitiveness. This study offers theoretical novelty by modeling the combined behavioral and innovation effects of GHRM in a service-based, emerging economy context. From a practical perspective, the results -provide insights for tourism regulators and business leaders that are seeking to align human resource strategies with China Sustainable Enterprise (CHSE) standards standards, green certifications, and Indonesia’s national sustainability agenda.